Cinderellis and the glass hill - Elliott, Mark (HarperCollins Publishers, 2000)
In this humorous retelling of a Perrault tale, a lonely young farm lad uses his unusual inventive ability to pass a nearly impossible test and win the hand of the neighboring princess.